Construction of p66Shc gene interfering lentivirus vectors and its affections on alveolar epithelial cells apoptosis induced by hyperoxia - Zhang C; Dong WB; Zhao S; Li QP; Kang L; Lei XP; Guo L; Zhai XS (Dove Medical Press, 2016)
Chan Zhang, Wen-Bin Dong, Shuai Zhao, Qing-Ping Li, Lan Kang, Xiao-Ping Lei, Lin Guo, Xue-Song Zhai Department of Newborn Medicine, Affiliated Hospital of Luzhou Medical College, Luzhou, Sichuan, People’s Republic of China Background: The aim of this study is to observe the inhibitive effects of p66Shc gene interfering lentivirus vectors on the expression of p66Shc, and to explore its effects on alveolar epithelial cells apoptosis induced by hyperoxia. Methods: The gene sequences were cloned into the pLenR-GPH-shRNA lentiviral vector, which was selected by Genebank searches. The pLenR-GPH-shRNA and lentiviral vector packaging plasmid mix were cotransfected into 293T cells to package lentiviral particles. Culture virus supernatant was harvested, and then the virus titer was determined by serial dilution assay. A549 cells were transduced with the constructed lentiviral vectors, and real-time polymerase chain reaction (RT-PCR) and Western blot were used to evaluate p66Shc expression. This study is divided into a control group, a hyperoxia group, an A549-p66ShcshRNA hyperoxia group, and a negative lentivirus group. Cell apoptosis was detected by flow cytometry after 24 hours; the expression of X-linked inhibitor of apoptosis protein (XIAP) and caspase-9 were detected by immunohistochemistry assay. The production of reactive oxygen species and cellular mitochondria membrane potential (ΔΨm) were determined by fluorescence microscopy. Results: We successfully established the p66Shc gene interfering lentivirus vectors, A549-p66ShcshRNA. The A549-p66ShcshRNA was transfected into alveolar epithelial cells, and the inhibitive effects on the expression of p66Shc were observed. Both RT-PCR and Western blot demonstrated downregulation of p66Shc expression in A549 cells. In the A549-p66ShcshRNA hyperoxia group, we found dampened oxidative stress. A549-p66ShcshRNA can cause p66Shc gene silencing, reduce mitochondrial reactive oxygen species generation, reduce membrane potential decrease, reduce the apoptosis of A549 cells, and reduce alveolar epithelial cell injury, while the lentiviral empty vector group had no such changes. Conclusion: p66Shc gene interfering lentivirus vector can affect the alveolar epithelial cells apoptosis induced by hyperoxia. Keywords: hyperoxia, alveolar epithelial cells, lentiviral vector, RNA interference, p66Shc, apoptosis